Comparative analysis of the role of sub-national parliaments in international human rights law in Nigeria and South Africa - Steytler, N.C. (Nico) (University of Pretoria, 2011)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2010.